(untitled) (Advancements in Homeopathic Research, 2022)
High blood pressure is classified as either primary high blood pressure or secondary high blood pressure. About 90–95% of cases are primary, defined as high blood pressure due to nonspecific lifestyle and genetic factors. Lifestyle factors that increase the risk include excess salt, excess body weight, smoking, and alcohol. The remaining 5–10% of cases are categorized as secondary high blood pressure, defined as high blood pressure due to an identifiable cause, such as chronic kidney disease, narrowing of the kidney arteries, an endocrine disorder, or the use of birth control pills. Now a days there is a high rise in patients of hypertension in our country. Hypertension is an “iceberg” disease. It is that only about half of the hypertensive people are aware of the condition , about half of those aware of the problem are being treated and only about 50% of those treated are considered adequately treated. Till today the measurement of pulse and blood pressure are not always taken as a routine work by professional’s thereby missing serious disease diagnosis like “ Hypertension”. This article will help professionals to overcome such problems and consider the seriousness of the facts in Homoeopathic practice. In this random study, 98 patients were considered for Homoeopathic treatment for over a period of two years, out of which 76 patients were recovered and the rest either dropped out or failed in recovery.